DEVELOPMENT OF THE DIGITAL STORY BOOK ’LALU DIA LALA JINIS’ AS A LEARNING MEDIA FOR 5TH GRADE ELEMENTARY SCHOOL STUDENTS - Ida Bagus Kade Gunayasa; I Ketut Widiada; Moh. Irawan Zain; Muhammad Tahir; Lalu Wira Zain Amrullah (PROGRES PENDIDIKAN, 2023)
The Sumbawa folklore book is currently a story book whose existence is not well identified. This can be proven by the fact that there are not many Sumbawa folklore books that can be used in learning at school or stored in the national library. In this regard, this study aims to design a digital storybook model, determine readability and determine the feasibility of digital Sumbawa folk stories that were tested on fifth grade students at Gusus 2 Elementary School, Sumbawa Besar. The method used in this study is Research and Development using the ADDIE model. The results of each stage of the research are detailed as follows; 1) at the analysis stage from the observations it was found that the use of folklore books was limited to limited printed textbooks and had not yet used storybooks in digital form, 2) at the design stage an update of the storybook model was produced from the printed version to the digital version as well as improving the display quality such as improvements visual, 3) at the development stage changes the shape of the cover image, adding color to the character of the character which was previously black and white, adjusting the vocabulary and story content which is then assessed by media experts and material experts with a feasibility level of 92.5% and 82.5% , 4) in the implementation stage which involved respondents from teachers and students produced a feasibility level of 91% and 98%, 5) the final stage, namely the evaluation stage by reviewing all the results obtained so that it can be concluded that the use of Sumbawa folk digital story books is very feasible for used as a learning medium in 5th grade elementary school Group 2 Sumbawa Besar.